2016
DOI: 10.1590/1678-4162-7866
|View full text |Cite
|
Sign up to set email alerts
|

Valores energéticos de rações expandidas em diferentes temperaturas para frangos de corte

Abstract: RESUMO O objetivo deste estudo foi determinar os valores energéticos de rações expandidas, obtidas em diferentes temperaturas de expansão para frangos de corte em diferentes idades. As rações foram expandidas nas temperaturas: 80; 100; 120; 140ºC. Dois ensaios biológicos foram conduzidos utilizando-se o método tradicional de coleta total de excretas para determinar a energia metabolizável aparente corrigida (EMAn). Os ensaios metabólicos foram conduzidos com pintos machos Cobb, de 11 a 19 dias (fase inicial) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The lower metabolizable energy noted in the extruded feed, can be related to the undesirable modifications in the feed nutrients, such as the formation of starch retrogradation, impairing glucose availability (Abdollahi et al, 2011;Liu et al, 2013). Starch retrogradation or type 3 resistant starch is not digested by pancreatic amylase, thus, it does not release glucose for absorption (Wang et al, 2015) and impairs energy production (Lima et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The lower metabolizable energy noted in the extruded feed, can be related to the undesirable modifications in the feed nutrients, such as the formation of starch retrogradation, impairing glucose availability (Abdollahi et al, 2011;Liu et al, 2013). Starch retrogradation or type 3 resistant starch is not digested by pancreatic amylase, thus, it does not release glucose for absorption (Wang et al, 2015) and impairs energy production (Lima et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Muramatsu et al (2013) also observed that expanding soybean meal at 130-136 °C decreased protein solubility in KOH from 80.57% to 64.12%. However, Lima et al (2016) observed that the thermal processing provided better availability of the protein from the hydrolysis of the starch present in the tested feeds.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 94%
“…Também houve redução no teor de EE e, Brazilian Journal of Development, Curitiba, v.7, n.3, p. 22473-22486 mar 2021 consequentemente, de EB, provavelmente em decorrência da desnaturação de ácidos graxos durante as duas peletizações. Lima et al (2016), ao realizar um experimento com diferentes temperaturas de expansão de ração para frangos de corte, observaram que a energia metabolizável corrigida reduziu em função do aumento na temperatura de expansão. Em experimento com frangos de corte de diferentes idades, Portella et al (1988) observaram maior produção de finos em animais jovens, o que elevou a quantidade de cálcio ingerida.…”
Section: Variáveisunclassified